High synthetic cost-amino acids reduce member interactions of acetate-degrading methanogenic microbial community - Yao, Jian; Zhang, Quan; Gou, Min; Tang, Yue-Qin (Frontiers in Microbiology, 2024)
The cooperation among members of microbial communities based on the exchange of public goods such as 20 protein amino acids (AAs) has attracted widespread attention.How the availability of AAs in the environment affects the interactions among members and the structure and function of a community is a core issue. This issue has only been studied in artificially constructed flora and has not yet been explored in natural complex microbial communities. To further validate the effect of AA accessibility on complex microbial communities and its mechanism of action, trace amounts of AAs combinations with different synthetic costs (low-cost, medium-cost, high-cost, and all 20 AAs) were supplemented separately to acetate-degrading thermophilic methanogenic reactors, and the differences in microbial community structure and cooccurring networks of main members were compared to a control reactor without AA supplementation. The structure of the microbial community and the interaction of community members were influenced by AAs supplementation and the AAs with different synthetic costs had different impacts. The number of nodes, links, positive links, and the average degree of nodes in the co-occurrence network of the microbial communities with AAs supplementation was significantly lower than that of the control without AAs supplementation, especially for all 20 AAs supplementation followed by the medium-and high-cost AAs supplementation. The average proportion of positive interactions of microbial members in the systems supplemented with low-cost, medium-cost, high-cost, all AAs, and the control group were 0.42, 0.38, 0.15, 0.4, and 0.45, respectively. In addition, the ecological functions of community members possibly changed with the supplementation of different cost AAs. This study provides meaningful references to the effects of public goods accessibility on the interactions among members of complex microbial communities, as well as on community function.